Development of marketing basics materials at SMKN 1 Bandung: Navigating technological disruption - Indah Ayulia; Nida Azka Pauziyyah; Raditya Rama Auda (Curricula: Journal of Curriculum Development, 2024)
This article explores the development of marketing fundamentals materials at Sekolah Menengah Kejuruan Negeri (SMKN) 1 Bandung in response to digital technology disruption. This disruption has fundamentally changed the business landscape and requires education at SMKN 1 Bandung to adapt so that students can face this challenge competently. The research method used is the descriptive Research Method. The article also discusses the various challenges faced by SMKN 1 Bandung in integrating digital marketing concepts into their curriculum and how interviews can be an effective tool in identifying suitable solutions. In this context, the article discusses strategies such as faculty training, curriculum updates, and utilization of digital technology in learning. The results of this study offer a profound understanding of the impact of digital technology disruption on marketing education at SMKN 1 Bandung. The key findings revealed through interview-based approaches provide valuable insights that other schools can apply. This research not only assists SMKN 1 Bandung in addressing the challenges of technological disruption but also provides a framework that other educational institutions can adopt.